If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7h=-9h-6
We move all terms to the left:
-7h-(-9h-6)=0
We get rid of parentheses
-7h+9h+6=0
We add all the numbers together, and all the variables
2h+6=0
We move all terms containing h to the left, all other terms to the right
2h=-6
h=-6/2
h=-3
| 15-9y=47-25y | | 120=12k+29 | | -93=-2n-7(n+3) | | k2− 2=1 | | 39+11=2x+3 | | (2x-1)+(6x-19)=180 | | 20=x/4=8 | | -5k+7=-k-9 | | y+11/6=1 | | 3.3w-9=-22. | | x-7+2x-10=10 | | 5n=3n=8 | | y=20/4-8 | | 2x+3+11=39 | | 230x=35x-1000 | | 4x-2=1.666666667 | | -7q=6-6q | | 6(x-5)=4(x+7) | | (Y+19)+(6x-19)=180 | | -30-8c=2c | | 6(x-5)=4(x+7) | | 4x-2=5/3 | | -1-5r=-10-6r | | 5x+4=-7x-4 | | −12x=−5 | | 0.6n-0.02+0.3n=0.61 | | 7−3z=10 | | 26+6b=2(3b+4 | | 250=2.5z | | 2z+8=4 | | -84=3(-8x-4) | | -2p=-10+3p |